Gamification approach toward flexibility learning: MyHSC apps - Mohamed, Rozihan; Mat Su, Ahmad Suhaizi (Centre for Global Open Access Learning, Immersive Technology & Quality Assurance, Universiti Sains Islam Malaysia, 2017)
In the context of the increasingly changing and evolving landscape of higher education, flexible learning is the future of higher education which brings the goal of access to education at any time, by anyone, and anywhere. The approach to flexible learning can be improved through innovations that are recognized as gamification. The smartphones application such as Android or iOS platform has enabled stakeholders in biodiversity to connect the ubiquity of these platforms and create various types of mobile applications as a tool in biodiversity and conservation research. The interactive functionalities such as gamification via smartphone have designed for public and biodiversity researchers to identify, obtain and record biodiversity data as well as generating knowledge portability in the digital forms. The gamification involves the use of game elements in non-game contexts and enable users to utilize computational ability to discover the enjoyment of species identification which previously reserved for biodiversity experts. However, apparently there is lack of mobile application gamification devoted to the identification in horseshoe crab species. This gamification of species identification app facilitated user to identify the species as well as accompanying with field guide. This innovation enable user (student/public) to comprise with main species information, image capturing, geolocation and geotagging which will assists and ease the users to identify and record the information during conservation/field work. Perhaps, MyHSC app gamification of horseshoe crab species identification will create an impetus to the interest and enhancement engagement of student in species identification as well as increasing awareness among public for species conservation in Malaysia.